2021
DOI: 10.3390/ph14070694
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cyanine Dye NK-4 on Photoreceptor Degeneration in a Rat Model of Early-Stage Retinitis Pigmentosa

Abstract: The present study aimed to evaluate the effects of NK-4 on the apoptosis of photoreceptors in a rat model of retinitis pigmentosa and explore the mechanism underlying anti-apoptosis activity. The Royal College of Surgeons (RCS) rats received an intravitreous injection of NK-4 solution in the left eye and vehicle control in the right eye. Apoptosis was detected by TUNEL method in frozen sections of the eyes. The retinal tissues of the rats were dissected for RNA-seq analysis. Functional and pathway enrichment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The use of antioxidants such as curcumin ( 33 ), taurododecoxycholic acid (TUDCA) ( 34 ), n-acetylcysteine ( 35 ), lutein ( 36 ), and chlorogenic acid ( 37 ) can temporarily improve vision in PR patients. Besides, a recent study suggested that genetic mutations and overload of intracellular metal ions may cause deficiency or excess of metal ions, including Fe, Cu, and Zn, disrupting retinal metal homeostasis ( 38 ). The above results are consistent with our GO enrichment results, suggesting that RALRG can exert protective effects through multiple biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antioxidants such as curcumin ( 33 ), taurododecoxycholic acid (TUDCA) ( 34 ), n-acetylcysteine ( 35 ), lutein ( 36 ), and chlorogenic acid ( 37 ) can temporarily improve vision in PR patients. Besides, a recent study suggested that genetic mutations and overload of intracellular metal ions may cause deficiency or excess of metal ions, including Fe, Cu, and Zn, disrupting retinal metal homeostasis ( 38 ). The above results are consistent with our GO enrichment results, suggesting that RALRG can exert protective effects through multiple biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Eight male pink-eyed RCS (Jcl-rdy/rdy, p-) rats were obtained from CLEA Japan, Inc. (Tokyo, Japan), and reared under a 12 h light/dark cycle. All intravitreal injections were performed as described previously [6]. At the age of 3 and 4 weeks, the rats were anesthetized by intraperitoneal injection of ketamine (87 mg/kg body weight, Daiichi Sankyo, Tokyo, Japan) and xylasine (13 mg/kg, Bayer Japan, Osaka, Japan), and received an intravitreal injection of 5 µL of NK-5962 solution at 8.2 µg/mL (16 µM) in the left eye, and saline (0.9% sodium chloride) as a vehicle control in the right eye, with a 30-gauge needle-attached Hamilton syringe (50 µL 1705 LT SYR; Hamilton Company, Reno, NV, USA) under a dissecting microscope.…”
Section: Animalsmentioning
confidence: 99%
“…Patients with RP experience slowly progressive loss in the peripheral visual field, finally leading to blindness in later decades [1]. Nowadays, many treatments including neurotrophic factors [2,3], antioxidants [4][5][6], retinal prostheses [7][8][9][10][11][12], and gene therapies [13] are used to rescue retinal degeneration and improve the visual function.…”
Section: Introductionmentioning
confidence: 99%